Demographic Profile and Pattern of Death of Foetus and Infants: An Autopsy Based Study in Indore District (MP) - Rastogi, Ashok K; Singh, Bajrang K; Dadu , Sanjay K (Journal of Indian Academy of Forensic Medicine, 2016)
It is a post-mortem based study, in this study infant and foetus included. Total 32 cases included  out of which 29 cases foetus and 03 cases were infants. Out of which 53.13% cases were female, 25%  cases were male and 21.88% cases sex could not determine. Most of the foetus died in 2nd & 3rd trimester  contributing 75% cases, most commonly in 2nd trimester 43.75% cases followed by 3dr trimester 31.25%  cases. Least number of cases had seen in first trimester 15.63%. Maximum numbers of cases was still  birth 59.38%. After autopsy examination we found there were 50% cases in advance stage of  decomposition and 50% (16) cases were in early stage of decomposition or decomposition not started.  Even after implementation of strong act pre conceptional & prenatal diagnostic technique act (PC &  PNDT Act), it is not so effective to control female feticide and infanticide. Premarital affairs are increasing  the cases day by day resulting increasing illegal abortion day by day.
Keywords: Infant; Foetus; Still birth; Decomposition; Autopsy examination; Trimester